Geospatial modelling of shear-wave velocity and fundamental site period of Quaternary marine and glacial sediments in the Ottawa and St. Lawrence Valleys, Canada. Issue 85 (June 2016) - Nastev, Miroslav; Parent, Michel; Ross, Martin; Howlett, Danielle; Benoit, Nicolas
Abstract: The shear wave velocity of surficial sediments ( V S ) and the fundamental site period ( T O ) are important parameters for analysis of the free-field seismic response. Their spatial distribution in the Ottawa and St. Lawrence Valleys, Canada, was determined applying a standardized method consisting of (i) updating the Quaternary geology; (ii) classifying the surficial units with similar physical properties into three broad categories: upper sandy sediments, intermediate clayey sediments and basal glacial and non-glacial deposits; (iii) delineating the spatial thickness of each category by way of 3D geologic modelling; (iv) sorting of available geophysical data with respect to each individual category and assigning representative VS relationships: a power velocity-depth function for sand and clay units combined, V S =119+8.1 Depth 0.5 (m/s), and a constant interval V S equal to the observed geometric mean velocity for glacial and non-glacial deposits, V S =385 (m/s). The respective T O values were computed as the ratio between the soil thickness and the average V S from ground surface to the bedrock. Validation of model results was conducted with V S and T O field data and available T O estimates from detailed urban-scale seismic zonation studies. The analyses of the uncertainty originating from the variation of the V S measurements showed that the standard deviations were roughly one-third of the modelled V S and T O values.